2011
DOI: 10.1111/j.1468-2397.2011.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Iraqi refugees and the humanitarian costs of the Iraq war: What role for social work?

Abstract: Harding S, Libal K. Iraqi refugees and the humanitarian costs of the Iraq war: what role for social work? The US‐led invasion and war in Iraq has created one of the most significant refugee crises in recent decades. International nongovernmental organizations have partnered with local organizations in Jordan and Syria to provide humanitarian aid to some two million displaced Iraqis. Field research indicates that, as with other humanitarian crises, few trained social workers have contributed to policy and pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…There is a considerable social cost to forced displacement that needs specialized professional services in the humanitarian field (Harding & Libal, 2012). Roberts and Browne's (2011) literature review showed a strong negative influence of forced migration on mental health, and found that mental health risk factors for populations affected by war in low/middle income countries are different from those who are in high income countries.…”
Section: Mental Health and Psychosocial Support Effects Of War On Menmentioning
confidence: 99%
“…There is a considerable social cost to forced displacement that needs specialized professional services in the humanitarian field (Harding & Libal, 2012). Roberts and Browne's (2011) literature review showed a strong negative influence of forced migration on mental health, and found that mental health risk factors for populations affected by war in low/middle income countries are different from those who are in high income countries.…”
Section: Mental Health and Psychosocial Support Effects Of War On Menmentioning
confidence: 99%
“…These may be brought on by the stress of residing in refugee camps or the required adjustments to life in the U.S. (Jamil et al, 2005). Several studies have identified pre-and post-migration experiences that increase newcomer susceptibility to emotional distress (Harding & Libal, 2012;Jamil & Ventimiglia, 2010;Montgomery et al, 2014;Schweitzer, Melville, Steel, & Lacherez, 2006;Willard, Rabin, & Lawless, 2014). Furthermore, within some communities of resettled refugees, the suicide rate may be more than three times as high as in the general U.S. population (Refugee Health Technical Assistance Center, n.d.).…”
Section: Refugee Mental Health Concernsmentioning
confidence: 99%
“…While literature in working effectively with refugees has flourished in related helping professions including social work (Austin, & Este, 2001;Deacon, & Sullivan, 2009;Harding & Libal, 2012) and health care (Barko, Farkhouri, & Arnetz, 2011;Jamil et al, 2005;Prince et al, 2007), there is a dearth of literature in professional counseling journals specific to this population. The purpose of this paper is to provide counselors with information specific to the refugee experience and strategies for working with this population.…”
mentioning
confidence: 99%
“…Since its inception, the social work profession has maintained a strong commitment to w orking with disenfranchised populations. Social workers have done extensive work with people who are impoverished and oppressed, yet, as a profession, social workers have done comparatively little work with refugees (Harding and Libal 2012). Refugees typically experience dislocation, persecution, and significant cultural adjustments, making them a highly vulnerable population deserving more attention from social work and other helping professions (Weaver and Burns 2001).…”
mentioning
confidence: 99%